The first record of the butterfly Memphis d. dia(Lepidoptera: Nymphalidae, Charaxinae) in Costa Rica - Córdoba-Alfaro, Jim (2012)
The presence of Memphis diain Costa Rica (Godman & Salvin, 1884) (Lepidoptera: Nymphalidae, Charaxinae) is reported herein, based on a specimen collected El Rodeo (09 ° 54’ 76.6”N; 84 ° 16’ 89.5”W) on April 4, 2012.